Human Resources Performance Improvement Through Training During the Covid-19 Pandemic - Fajar Rezeki Ananda Lubis; Syaifuddin; Yusniar Lubis (GoAcademica Research & Publishing, 2022)
For human resource management, making improvements to human resources is one of the essential factors to be able to improve and optimize company performance. This increase can then be carried out through the implementation of training, including during the Covid-19 pandemic. This research will then try to see how the performance of human resources can be improved through the implementation of training during the Covid-19 pandemic. This research will be carried out using a qualitative approach as the research method. The results of this study found that the implementation of training was crucial for improving human resources’ performance even though there was a pandemic. In order to reduce the risk of a pandemic, it is necessary to change the training method for improving the performance of appropriate human resources, so that finally the training can carry out its role correctly in enhancing the performance of human resources, and protocols are still followed so that there is no spread of the Covid-19 virus in the future.